Advancing NMDA Receptor Physiology by Integrating Multiple Approaches. Issue 3 (March 2017) - Zhou, Huan-Xiang; Wollmuth, Lonnie P.
Abstract : NMDA receptors (NMDARs) are ion channels activated by the excitatory neurotransmitter glutamate and are essential to all aspects of brain function, including learning and memory formation. Missense mutations distributed throughout NMDAR subunits have been associated with an array of neurological disorders. Recent structural, functional, and computational studies have generated many insights into the activation process connecting glutamate binding to ion-channel opening, which is central to NMDAR physiology and pathophysiology. The field appears poised for breakthroughs, including the exciting prospect of resolving the conformations and energetics of elementary steps in the activation process, and atomic-level modeling of the effects of missense mutations on receptor function. The most promising strategy going forward is through strong integration of multiple approaches. Trends: The number of iGluR structures, both for isolated domains and for C-terminal domain (CTD)-truncated constructs, has expanded drastically in the Protein Data Bank. The extracellular domains usually display ligand-induced structural changes, but the transmembrane layer has yet to be captured in an open-pore conformation. Electrophysiological data, interpreted with the help of available structures, have defined the contributions of key gating elements, in particular the M3 helix and the M3–D2 linker, to channel activation. Single-channel data can further determine the energetics and kinetics, but not conformations, of substates along the activation pathway. Computational studies have so far focused on motions within isolated domains or over very short timescales, but atomic-level modeling is becoming feasible to calculate gating energetics and kinetics. The NMDAR field appears poised for breakthroughs, but urgently needs strong integration of multiple approaches.